Environmental vs. spatial drivers of submerged macrophyte community assembly in different seasons and water depths in a mesotrophic bay of Erhai Lake, China. (October 2020) - Wang, Hao; Wen, Zihao; Zhang, Zhonghai; Zhang, Xiaolin; Fu, Hui; Cao, Yu; Ni, Leyi; Cao, Te; Li, Kuanyi
Graphical abstract: Highlights: Environmental and spatial drivers function together to regulate species diversity at one fine scale. The relative contribution of environmental and spatial drivers to community assembly varies seasonally. Community assembly mechanisms of submerged macrophytes in shallow and deeper water areas are different. Abstract: The relative importance of environmental and spatial drivers in shaping local plant diversity patterns remains unclear. Here, we investigated the environmental and spatial drivers regulating species composition of the submerged macrophyte community in Erhai Lake, China, over different seasons and water-depth gradients. Results showed that environmental and spatial drivers significantly affected species composition of the submerged macrophyte community at the local and fine scale, with shared environmental and spatial drivers explaining 28.3%–38.4% of the variation in species composition for all four seasons. The unique spatial drivers demonstrated a relatively stable contribution (11.8%–16.0%) over the four seasons, but the contributions from the unique environmental drivers showed seasonal variability, being high in summer and winter. In shallow water (0–3 m), spatial drivers were more important in the process of community assembly; in deep water (3–6 m), however, environmental and spatial drivers both significantly affected community assembly. The different water areas also showed strong seasonal changes in the explanatory power of environmental and spatial drivers of submerged macrophyte community variation. Thus, future studies should consider sampling macrophytes over different seasons and at different water depths to better trace the indicators regulating submerged macrophyte community assembly in lakes.